Playing the game - Bradford, Barbara Taylor, 1933- (New York : St. Martin's Press, 2010)
When Annette Remington's husband and mentor, the much older Marius Remington, handpicks journalist Jack Chalmers to do a profile on his beloved wife in a popular London Sunday newspaper, he never intends to put his marriage in jeopardy. How could he have known that the connection between Jack and Annette would ignite so many secrets? And how could he know that Jack would uncover a scandal that could ultimately destroy them all?
London, March 2007 -- Remarkable woman -- Hotshot journalist -- Dangerous encounter -- Accidental informant -- London, December 2007.
Includes bibliographical references (p. [389]-390).
Keywords: 0 Women art dealers -- Fiction; 0 Husband and wife -- Fiction; 0 Journalists -- Fiction; 0 Secrecy -- Fiction; 0 London (England) -- Fiction